Gellan gum-based delivery systems of therapeutic agents and cells. (1st February 2020) - Palumbo, Fabio Salvatore; Federico, Salvatore; Pitarresi, Giovanna; Fiorica, Calogero; Giammona, Gaetano
Abstract: The purpose of this review is to make a summary of high quality research trends using gellan gum (GG) as a polymeric constituent for the design of innovative drug delivery systems and devices for biomedical applications, such as cell therapy and regenerative medicine. The use of gellan gum is described both in its native form and as chemically functionalized derivatives or physically mixed with natural or synthetic materials. Starting from a systematic study of recent research works, the main properties of the native polysaccharide have been highlighted and therefore some improvements have been focused thanks to the design of chemically functionalized derivatives and the use of composite materials.